Comparison of Different Treatment Modalities Outcomes in Clinically Node-positive Bladder Cancer: Analysis of a Population-based Cancer Registry - Staník, Michal; Poprach, Alexandr; Zapletalová, Michaela; Krejčí, Denisa; Macík, Daniel; Čapák, Ivo; Jarkovský, Jiří; Lakomý, Radek; Doležel, Jan (Clinical genitourinary cancer, 2019)
INTRODUCTION: Patients with clinically node-positive bladder cancer were historically considered to have uniformly poor prognosis and were frequently treated with palliative chemotherapy (CHT) only. Although retrospective data show that long-term survival with combined treatment (surgery + CHT) is possible in one-third of these patients, consensus on a treatment algorithm is still lacking. The aim of the study is to compare the efficacy of different treatment modalities based on data from a population-based cancer registry. PATIENTS AND METHODS: The study comprises 661 patients identified from the Czech National Cancer Registry (1996-2015) with cTanyN1-3M0 bladder cancer; 195 were treated with CHT alone, 234 underwent radical cystectomy alone (RC), and 232 received a combination of RC and perioperative CHT (RC + CHT). Multivariate Cox proportional hazard regression analyses were used to evaluate the effectiveness of various treatments. RESULTS: The 5-year OS for CHT alone, RC alone, and RC + CHT were 21.7% (95% confidence interval [CI], 15.4%-28.0%), 12.1% (95% CI, 7.4%-16.7%), and 25.4% (95% CI, 18.9%-31.9%), respectively (P < .001). The median survivals were 17, 10, and 23 months, respectively. In multivariate analysis, age > 60 years (hazard ratio, 1.29; 95% CI, 1.06-1.56; P = .011) and clinical stage cT3-4 (hazard ratio, 1.39; 95% CI, 1.12-1.71; P = .002) were negative predictors of survival. When compared with CHT, RC + CHT reduced the risk of overall mortality by 21% (P = .044). CONCLUSION: Approximately one-quarter of clinically node-positive patients may achieve long-term survival with combined treatment integrating RC and perioperative CHT. The overall survival of patients is significantly improved with a multimodal approach in comparison to CHT alone.
Keywords: Registries; kombinovaná terapie; proporcionální rizikové modely; Humans; lidé středního věku; Proportional Hazards Models; analýza přežití; Combined modality therapy; registrace; Chemotherapy, Adjuvant; Chemotherapy; Female; Aged; výsledek terapie; Cystectomy; senioři; lidé; Lymphatic Metastasis; Survival Analysis; adjuvantní chemoterapie; lymfatické metastázy; Urinary bladder neoplasms; staging nádorů; ženské pohlaví; Kaplanův-Meierův odhad; Male; nádory močového měchýře; Middle Aged; Retrospective Studies; Treatment Outcome; Czech Republic; Lymphadenopathy; retrospektivní studie; Kaplan-Meier Estimate; Neoplasm Staging; cystektomie; Česká republika; mužské pohlaví; Combined Modality Therapy; Urinary Bladder Neoplasms